Family and sustainable development - Cavallotti, Rita; Gas Aixendri, Montserrat (Cizur Menor, Navarra Aranzadi, 2015)
Family is not only the fundamental group unit of society, but it is also the fundamental agent for sustainable, social, economic and cultural development. This book delves into this reality and invites to reflect about it. The volume compiles in a rigorous and structured way the contributions of more than twenty professors from universities around the world form different scientific fields of expertise. Care of elderly and children, Work-Family balance, Immigration, Education, Social participation, Employment, School, Religion, Intergenerational Solidarity and Family structure are some of the key topics of this publication. The issues are dealt with scientific rigor but with straightforward vocabulary therefore this book is of interest not only to academics but to anyone who is interested in exploring the irreplaceable social role of the family.
Keywords: Derecho civil